A Polymer Coating Transfer Enrichment Method for Direct Mass Spectrometry Analysis of Lipids in Biofluid Samples. (27th March 2019) - Zhang, Wenpeng; Chiang, Spencer; Li, Zishuai; Chen, Qinhua; Xia, Yu; Ouyang, Zheng
Abstract: A porous polymer coating transfer enrichment method is developed for the direct mass spectrometry (MS) analysis of lipids. The enrichment is fast (ca. 1 min) and enables the profiling and quantitation of lipids in small‐volume biofluid samples. Coupled with a photochemical Paternò–Büchi reaction, this method enables the fast determination of lipid structure at the C=C location level and point‐of‐care lipid biomarker analysis.